1998
DOI: 10.1002/hep.510280624
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Taurocholate Cotransporting Polypeptide Is A Serine, Threonine Phosphoprotein and Is Dephosphorylated by Cyclic Adenosine Monophosphate

Abstract: Na ؉ /taurocholate (Na ؉ /TC) cotransport in hepatocytes is mediated primarily by Na ؉ /TC cotransporting polypeptide (Ntcp), and cyclic adenosine monophosphate (cAMP) stimulates Na ؉ /TC cotransport by inducing translocation of Ntcp to the plasma membrane. The aim of the present study was to determine if Ntcp is a phosphoprotein and if cAMP alters Ntcp phosphorylation. Freshly prepared hepatocytes from rat livers were incubated with carrier-free 32 PO 4 for 2 hours, followed by incubation with 10 mol/L 8-chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…We have reported previously (10) that the stimulatory effect of cAMP on Na ϩ /TC cotransport is potentiated by cAMP-induced increases in cytosolic [Ca 2ϩ ]. We also observed that cAMP failed to increase plasma membrane Ntcp when cytosolic Ca 2ϩ was buffered (15). Since okadaic acid inhibited the ability of cAMP to increase cytosolic [Ca 2ϩ ] (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We have reported previously (10) that the stimulatory effect of cAMP on Na ϩ /TC cotransport is potentiated by cAMP-induced increases in cytosolic [Ca 2ϩ ]. We also observed that cAMP failed to increase plasma membrane Ntcp when cytosolic Ca 2ϩ was buffered (15). Since okadaic acid inhibited the ability of cAMP to increase cytosolic [Ca 2ϩ ] (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Since treatment of hepatocytes with cAMP results in an increase in plasma membrane and a decrease in endosomal Ntcp mass, we proposed that cAMP increases transport maximum of Na ϩ /TC cotransport by translocating Ntcp from an endosomal pool to the plasma membrane (14). In addition, our recent study showed that Ntcp is a serine/threonine phosphoprotein, phosphorylated Ntcp is detectable in the plasma membrane, but not in microsomes and Golgi complex, and treatment of hepatocytes with cAMP results in Ntcp dephosphorylation (15). These results raise the possibility that the regulation of Na ϩ /TC cotransport by cAMP may also involve phosphorylation/dephosphorylation of Ntcp.…”
Section: Namentioning
confidence: 97%
“…On the posttranscriptional level, sodium-dependent and -independent hepatocellular uptake systems are mainly regulated by cyclic adenosine monophosphate-mediated dephosphorylation processes, which is controlled by phophoinositide-3-kinase/protein kinase B. [21][22][23] Furthermore, PDZK1 was demonstrated to be a critical determinant for the proper subcellular localization and function of rat Oatp1a1. 24 The transcriptional regulation of basolaterally expressed MRPs is not fully elucidated.…”
Section: Hepatic Transport Systemsmentioning
confidence: 99%
“…Conjugated bile acids, such as TC, are efficiently taken up by hepatocytes primarily via a Na ϩ /TC cotransport mechanism; Ntcp, a serine/threonine phosphoprotein (21), is believed to be the major protein involved in Na ϩ /TC cotransport (22)(23)(24). Cyclic AMP and cell swelling rapidly increase Na ϩ /TC cotransport and Ntcp translocation to the plasma membrane (25)(26)(27), and this effect is mediated via the PI3K/PKB signaling pathway (11).…”
Section: And P70mentioning
confidence: 99%